TRANSFORMATION OF SAMBER BINYERI MAJU COOPERATIVE: ASSISTANCE TOWARDS MODERN COOPERATIVES IN BIAK NUMFOR REGENCY, PAPUA - Yomungga, Moses; Kubelaborbir, Triana M. (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The Samber Binyeri Maju Cooperative in Biak Numfor Regency, Papua, is a cooperative engaged in the fisheries sector with the aim of improving the welfare of members through sustainable management of fishery resources. This study discusses the problems faced by cooperatives, the goals and methodology of the mentoring program carried out by the Modern Cooperative Assistance Team (TPKM), as well as the results of the implementation of the program. Through SWOT analysis and Business Model Canvas, this cooperative shows great potential to grow with the right support. The results of the assessment showed significant improvements in various aspects, including institutional, business, market, finance, and digitalization. This research also provides recommendations for the development of cooperatives in the future.